Chronic Histologic Changes Are Present Regardless of HLA Mismatches: Evidence from HLA-Identical Living Donor Kidney Transplants. Issue 11 (21st October 2021) - D'Costa, Matthew R.; Bentall, Andrew; Denic, Aleksandar; Schinstock, Carrie A.; Merzkani, Massini A.; Park, Walter D.; Ryan, Margaret S.; Alexander, Mariam P.; Smith, Byron H.; Gandhi, Manish J.; Stegall, Mark D.
Abstract : Background: At 5 and 10 y after kidney transplantation, chronic histologic changes such as arteriolar hyalinosis and mesangial expansion are common; however, determining cause is difficult. We compared surveillance biopsies in living donor kidney transplants (LDKTx) from HLA-matched siblings (termed HLA-identical [HLA-ID]) with HLA non-ID to investigate which histologic changes were likely due to alloimmune injury and which were due to nonalloimmune injury. Methods: We performed a retrospective, cohort study comparing HLA-ID sibling LDKTx (n = 175) with HLA non-ID LDKTx (n = 175; matched for age, sex, and year of transplant ±2 y) performed at a single institution from March 1999 to November 2018. Results: Baseline characteristics and maintenance immunosuppression were similar. Mortality rates were similar, but in the HLA-ID group, 10-y death-censored graft survival was higher (93.8% versus 80.9% HLA non-ID LDKTx; P  < 0.001), rejection rates were lower (after 1 y 9.6% versus 27.1%; P  < 0.001), and Banff inflammation scores including glomerulitis and peritubular capillaritis were lower on surveillance biopsies at 1, 5, and 10 y. In contrast, chronic Banff scores (interstitial fibrosis, arteriolar hyalinosis, mesangial expansion, etc) were similar in prevalence and severity on surveillance biopsies at 1, 5, and 10 y. Conclusions: HLA-ID LDKTx have less inflammation and less transplant glomerulopathy, but most chronic histologic changes were similar to less well-matched LDKTx. We conclude that these types of chronic changes are not associated with HLA mismatches and may be due to nonimmunologic causes (hypertension, obesity, etc), suggesting that new management approaches to prevent these lesions may be needed. Abstract :